FACTORIZATION PROPERTIES IN POLYNOMIAL EXTENSION OF UFR'S - Alan, Murat (YILDIZ TECHNICAL UNIV, 2005)
We investigate the factorization properties on the polynomial extension A[X] of A where A is a UFR and show that A[X] is a U-BFR for any UFR A. We also consider the ring structure A + XI[X] where A is a UFR.
Keywords: Factorization; Polynomial rings; Engineering